Academic Achievement in Chemistry Based on the 7E Learning Cycle Model in Jordanian High Schools - Alsalhi, Najeh Rajeh (Journal of International Students, 2023)
This study seeks to investigate the impact of implementing the 7E learning cycle model on the academic performance of high school students in Jordan. This study employed a quasi-empirical design. A sample size of 106 students enrolled at Ahmed Toukan Secondary School, a school located in Amman and affiliated with the Directorate of Education for Marka District, was employed in this study. The study sample consisted of two distinct groups:52 students in the empirical group, and 54 in the control.A teacher’s guide was developed based on the 7E learning cycle model, and an achievement test was created following the guidelines outlined in the good test specification table. Researchers have confirmed the validity and reliability of the subject matter. The results indicate a statistically significant difference between the two groups, with the empirical group being favoured.